COMPLEX QUINUCLIDINES (1-AZABICYCLO[2.2.2]OCTANES) FROM SUGARS - SYNTHESIS OF (1-ALPHA,3-ALPHA,4-ALPHA,5-ALPHA)-QUINUCLIDINE-3,5-DIOL FROM D-GLUCOSE - Fleet, G; Mathews, C; Seijas, J; Tato, M; Brown, D (1989)
The synthesis of (1α,3α,4α,5α)-quinuclidine-3,5- diol from D-glucose by two alternative ring closures is described.